Near-infrared spectroscopy (NIRS) in functional research of prefrontal cortex - Nobuo Masataka (Frontiers Research Topics, 2016)
This e-book includes the latest outcomes produced by a broad range of fNIRS research with activation of prefrontal cortex, from methodological one to clinical one, providing a forum for scientists planning functional studies of prefrontal brain activation. Reading this book, one will find the possibility that fNIRS could replace fMRI in the near future, and realize that even our aesthetic feeling is measurable. This will serve as a reference repository of knowledge from these fields as well as a conduit of information from leading researchers. In addition it offers an extensive cross-referencing system that will facilitate search and retrieval of information about NIRS measurements in activation studies. Researchers interested in fNIRS would benefit from an overview about its potential utilities for future research directions.